2020
DOI: 10.1080/22221751.2020.1770129
|View full text |Cite
|
Sign up to set email alerts
|

Profiling serum cytokines in COVID-19 patients reveals IL-6 and IL-10 are disease severity predictors

Abstract: Since the outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, China, it has rapidly spread across many other countries. While the majority of patients were considered mild, critically ill patients involving respiratory failure and multiple organ dysfunction syndrome are not uncommon, which could result death. We hypothesized that cytokine storm is associated with severe outcome. We enrolled 102 COVID-19 patients who were admitted to Renmin Hospital (Wuhan, China). All patients were classified into modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

81
972
3
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,043 publications
(1,146 citation statements)
references
References 28 publications
81
972
3
14
Order By: Relevance
“…Another survey in only 40 patients split into those requiring MV and admission in an intensive care unit (n=20) and into those with stable diseases showed similar increase of IL-6 among the most severe cases [13]. This was also the nding of a cohort comparing 17 patients with critical COVID-19 to 85 patients with mild or moderate disease [14]. The present study goes well beyond previous prospective cohorts since it demonstrates the importance of admission levels for the early prediction of the disease course.…”
Section: Discussionmentioning
confidence: 68%
“…Another survey in only 40 patients split into those requiring MV and admission in an intensive care unit (n=20) and into those with stable diseases showed similar increase of IL-6 among the most severe cases [13]. This was also the nding of a cohort comparing 17 patients with critical COVID-19 to 85 patients with mild or moderate disease [14]. The present study goes well beyond previous prospective cohorts since it demonstrates the importance of admission levels for the early prediction of the disease course.…”
Section: Discussionmentioning
confidence: 68%
“…While the number of animals enrolled in this study was not sufficient to look at species-specific differences and their effect on disease progression, we found that a higher ratio of IL-6:IL-10 cytokine in plasma was associated with disease severity. Undoubtedly, more studies are needed to prove or disprove the single contribution of IL-10 and IL-6 in the outcome of COVID-19 disease and to identify the source of these two potential key players 48 . Overall, this study uncovers critical steps in the immune events of the host response to SARS- Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, authors have demonstrated a direct correlation with IL6 serum levels, suggesting that both cytokines could be used as predictors of higher risk of disease deterioration [20]. Thus, despite its well-known antiin ammatory role, an exaggerated release of IL10, together with other pro-in ammatory factors from activated macrophages is integrated in the context of the cytokine storm and considered a marker of disease severity [21]. In the present study, however, there was no signi cant variation in IL10 BAL levels either in relation to disease severity or according to survival (Fig.…”
Section: Discussionmentioning
confidence: 99%